At freedom's door : African American founding fathers and lawyers in Reconstruction South Carolina - Underwood, James L.; Burke, William Lewis (University of South Carolina Press, 2000)
Bringing into focus a legacy not fully recognized, the contributors collectively demonstrate the legal acumen displayed by prominent African Americans and the impact these individuals had on the enactment of substantial constitutional reforms--many of which, though abandoned after Reconstruction, would be resurrected in the twentieth century.